2021
DOI: 10.1177/00208728211009579
|View full text |Cite
|
Sign up to set email alerts
|

Toward an inclusive digital economy for all: Perspectives from an intersectional feminist social work lens

Abstract: The digital global economy is increasingly becoming the economy. The current pandemic has accelerated the digitization of the economy as offline economic activities are suspended, and ‘going digital’ is touted as a survival strategy for economic sectors worldwide. In this conceptual article, I argue that this emerging economy is (re)producing social inequalities. Social workers need to be knowledgeable about the digital global economy and engage in economic justice initiatives to actualize social justice. I em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Kwan, C states that with the development of the pneumonia pandemic, traditional economic activities have received considerable impact, and the digital economy is a survival strategy for the current part of the economy. However, at the same time, the emerging digital economy is prone to social inequality, depicting a state of the field in which social workers are involved [17]. Giraudo, M explored the ways in which personal data drive economic activities in the context of the digital economy based on the theory of "legal bubbles" [18].…”
Section: Synthesis Of Researchmentioning
confidence: 99%
“…Kwan, C states that with the development of the pneumonia pandemic, traditional economic activities have received considerable impact, and the digital economy is a survival strategy for the current part of the economy. However, at the same time, the emerging digital economy is prone to social inequality, depicting a state of the field in which social workers are involved [17]. Giraudo, M explored the ways in which personal data drive economic activities in the context of the digital economy based on the theory of "legal bubbles" [18].…”
Section: Synthesis Of Researchmentioning
confidence: 99%
“…Shen, W et al investigated the data of the digital economy in different provinces of China in recent years to explore the coupling law between the digital economy and the high-level development of the economic system and explored the joint role and mutual influence of the two based on the coupled coordination model [14]. Kwan, C et al comprehensively studied the impact of the digital economy on traditional economic models and suggested that the digital economy is increasingly becoming a new driver of growth in the current world landscape, but it also brings new social injustices [15].…”
Section: Introductionmentioning
confidence: 99%